Long-acting high water-resistant degradable film and preparation method thereof
Patent Information
- Application Number
- CN202210672650.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-06-14
AI Technical Summary
CN 114163788 A公开了一种高强高阻隔生物降解薄膜的制备方法,关键点是使用电子束辐照分散纳米纤维素晶体使其获得较高的阻水和阻气性能,其阻隔机理是在材料内部形成更复杂的小分子通过路径,降低透气面积,从而增强阻隔性能,但是有着相同的缺陷是纳米纤维素晶体难以获取,并且加工难度较高
[0030] Compared with the prior art, the advantages of this invention are as follows:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable plastics, specifically relating to a long-lasting biodegradable film with high water resistance and its preparation method. Background Technology
[0002] With the continuous development of society and the economy, and the ongoing promotion of policies, biodegradable plastic products are gradually replacing traditional polyolefin products in various aspects. However, polyolefins have a natural advantage in water-blocking properties, while existing biodegradable plastics lag far behind. Therefore, there is an urgent need to improve the water-blocking properties of biodegradable plastics to expand their application range.
[0003] CN 113754995 A discloses a double-layer high-barrier, fully biodegradable mulch film that uses a blend of furanyl dicarboxylic acid-succinic acid-propylene glycol copolymer and polypropylene carbonate to enhance barrier properties. However, furanyl dicarboxylic acid-succinic acid-propylene glycol is not yet industrialized, and polypropylene carbonate has poor mechanical properties, failing to meet the needs of daily use of the film. CN 114108383 A discloses a biodegradable barrier material. This biodegradable barrier material includes a polyester emulsion, using polylactic acid emulsion or polycaprolactone emulsion blended with nano-cellulose crystals. Specifically, the emulsion and nano-cellulose crystals are mixed and then coated onto a paper-based material using an air knife. Barrier properties similar to PE can be obtained, but common grades of polylactic acid are all high molecular weight polymers, and there are no mature production methods for either emulsion polylactic acid or cellulose nanocrystals. CN 114163788 A discloses a method for preparing a high-strength, high-barrier biodegradable film. The key point is to use electron beam irradiation to disperse nanocellulose crystals to obtain high water and gas barrier properties. Its barrier mechanism is to form more complex small molecule passage paths inside the material, reduce the gas permeability area, and thus enhance the barrier performance. However, it has the same drawback: nanocellulose crystals are difficult to obtain and have high processing difficulty.
[0004] The permeation of water vapor through a membrane involves two steps: first, dissolution within the membrane; second, diffusion within the membrane; and finally, desorption. Current literature and patents focus on adding fillers inside the membrane to increase the permeation path and prevent water vapor diffusion. However, this approach is inefficient, and common mineral powders offer poor barrier properties. The advantage of this invention lies in establishing a hydrophobic small-molecule barrier layer on the surface of the biodegradable membrane. This layer provides barrier protection in the first step, enhancing barrier performance by preventing water vapor dissolution within the membrane. Furthermore, it leaves reaction sites, allowing the membrane to slowly absorb water, triggering a cross-linking reaction. The small-molecule barrier layer then adheres to the membrane surface, forming a long-lasting barrier. The processing method is extremely simple, requiring no modification to existing membrane processing equipment, and allows for large-scale production. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a novel water-blocking system. By adding hydrophobic additives during processing, a hydrophobic layer is formed on the film surface through self-crosslinking. Furthermore, by combining it with mineral powder, the water-blocking effect of the biodegradable film is greatly improved. Moreover, the process is simple and the application range is wider.
[0006] To achieve the above technical effects, the technical solution adopted by the present invention is as follows:
[0007] A long-lasting, highly water-resistant biodegradable film, the biodegradable film comprising the following components: 78.2–89.2 parts by weight of polybutylene adipate terephthalate (PBAT), 0.3–0.6 parts by weight of a hydrophobic additive, 0.5–1 parts by weight of a crosslinking agent, 0.5–1 parts by weight of a co-crosslinking agent, 10–20 parts by weight of mineral powder, 0.1–0.3 parts by weight of an initiator, and 0.1–0.3 parts by weight of a coating agent.
[0008] In this invention, the thin film comprises the following structure:
[0009]
[0010] Where m is an integer from 1 to 10, preferably an integer from 2 to 8; n is an integer from 1 to 10, preferably an integer from 2 to 6; and x is an integer from 10 to 30, preferably an integer from 18 to 22.
[0011] Unlike existing technologies that rely on adding mineral powder for barrier properties, this invention utilizes highly hydrophobic small molecules, such as glyceryl distearate, to rapidly migrate and spread on the film surface, forming a hydrophobic layer and leaving hydroxyl reaction sites. An amphiphilic coupling agent, after hydrolysis, couples with the hydroxyl groups of the hydrophobic small molecules in the film, immobilizing the small molecules within the film. An added co-crosslinking agent, through its epoxy functional groups, reacts with the residual hydroxyl and carboxyl groups of PBAT for grafting. The coupling agent, initiated by the free radical of di-tert-butyl peroxide (diisopropylbenzene), bridges the PBAT-grafted co-crosslinking agent, thus significantly extending the durability of the water-blocking agent. This reduces the water vapor permeability coefficient of the PBAT film to 10% of the original PBAT film and maintains good water-blocking performance for 8–10 months.
[0012] In this invention, the weight-average molecular weight of the PBAT is 80,000 to 230,000, preferably 120,000 to 180,000.
[0013] In this invention, the hydrophobic additive is a surface-active amphiphilic small molecule substance, preferably a hydroxyl-functionalized alkyl ester, more preferably one or more of glyceryl stearate, glyceryl betaine, and pentaerythritol stearate, and even more preferably one or more of glyceryl distearate, glyceryl monostearate, and glyceryl dibetaine.
[0014] In this invention, the crosslinking agent is a trimethoxysilane containing a double bond group, preferably γ-methacryloyloxypropyltrimethoxysilane and / or vinyltrimethoxysilane.
[0015] In this invention, the co-crosslinking agent is an olefin glycidyl ether, preferably vinyl benzyl glycidyl ether and / or allyl glycidyl ether, and more preferably allyl glycidyl ether.
[0016] In this invention, the mineral powder is montmorillonite with a layered structure, preferably octadecyl quaternary ammonium salt modified montmorillonite.
[0017] In this invention, the coating agent is a coordination phthalate, preferably tetraisopropyl di(dioctylphosphite)titanate.
[0018] In this invention, the initiator is a peroxide initiator, preferably one or more of dicumyl peroxide and bis-tert-butyl peroxide.
[0019] Another object of the present invention is to provide a method for preparing a long-lasting, highly water-resistant biodegradable film.
[0020] A method for preparing a long-lasting, highly water-resistant biodegradable film, wherein the biodegradable film is as described above, and the method comprises:
[0021] S1: The crosslinking agent, initiator, mineral powder and coating aid are mixed evenly using a high-speed mixer, and then fed into the twin screw from the side feed port.
[0022] S2: The hydrophobic additive is fed into the twin screw from the side feed port;
[0023] S3: Mix PBAT and crosslinking agent using a low-speed mixer, and then feed the mixture into the main feed port of the twin-screw extruder;
[0024] S3: Extruded by a twin-screw extruder, water-cooled, and granulated to obtain biodegradable long-lasting water-blocking composite material particles.
[0025] In this invention, the stirring speed of the mixer in S1 is 600-1000 r / min; the stirring speed of the mixer in S3 is 10-20 r / min; the length-to-diameter ratio of the screw of the twin-screw extruder in S3 is 56, the temperature is set in segments of 140-170℃, and the speed is 300-600 r / min, preferably 500 r / min.
[0026] In one embodiment, the crosslinking agent, co-crosslinking agent, and PBAT in the screw during step S1 mainly undergo the following reaction under the action of the initiator:
[0027]
[0028] In step S2, the hydrophobic additive and the crosslinking agent react as follows:
[0029]
[0030] Compared with the prior art, the advantages of this invention are as follows:
[0031] It significantly improves water resistance and extends the duration of water resistance. The water vapor transmission coefficient of PBAT film is reduced to 10% of that of the original PBAT film, and it can maintain good water resistance performance for 8 to 10 months. Attached Figure Description
[0032] Figure 1 The results are infrared tests of pure PBAT, hydrophobic additives, crosslinking agents, and modified PBAT after 30 days of soaking in Example 1. Detailed Implementation
[0033] Experimental reagents and instruments
[0034] PBAT, TH801T, Xinjiang Lanshan Tunhe; Hydrophobic additives, glyceryl distearate, 99.5% purity, Jinsheng New Material Technology Co., Ltd.; glyceryl disobrate, 99.5% purity, Xinxing Oils Co., Ltd.; Crosslinking agents, γ-methacryloyloxypropyltrimethoxysilane, vinyltrimethoxysilane, 99.5% purity, Kepler Biochemical Co., Ltd.; Co-crosslinking agent, allyl glycidyl ether, 99.5% purity, Kasno Technology Co., Ltd.; Montmorillonite, DK4, Zhejiang Fenghong; Coating agent, tetraisopropyl di(dioctylphosphite)titanate, 99% purity, Wuhan Huaxiang Biotechnology Co., Ltd.; PLA, FY804, Anhui Fengyuan; Chain extender, ADR4468, BASF;
[0035] The mechanical properties of the specimens were tested using an Instorn 5966 universal material testing instrument according to the national standard GB / T 1040.3-2006. The gauge length was 50 mm, the tensile speed was 500 mm / min, the sample width was 15 mm, the length was 150 mm, the test temperature was 23℃, and the humidity was 50%.
[0036] The water vapor barrier performance of the thin film was tested using a Jinan Sike WVTR-926 cup-type water vapor barrier tester in accordance with the national standard GB / T 1037-1988.
[0037] Infrared spectroscopy was performed using a NEXUS FT-IR transilluminator in accordance with the national standard GB / T 6040-2019, using total internal reflection mode, with a wavenumber range of 4000–400 cm⁻¹. -1 Between, with a resolution of 0.01cm -1Testing the thin film structure.
[0038] Six 500mm × 500mm sample films with a thickness of 40µm were cut. Three films were immersed in a 5L graduated cylinder, and the other three served as blank samples. All films were placed in a constant temperature and humidity chamber set at 23℃ and 50% humidity. After immersion for the set time, the test samples and blank samples were taken at the same time and placed in a 40℃ oven to dry for 24 hours. The water vapor permeability was tested simultaneously.
[0039] Twin-screw extruder: screw diameter 32mm, length-to-diameter ratio 52, Coperion, ZSK Mv PLUS;
[0040] Film blowing machine: screw diameter 35mm, length-to-diameter ratio 32, die diameter 80mm, die clearance 0.2mm, Zhejiang Yunfeng Machinery Factory, YFFE-800
[0041] Example 1
[0042] Weigh 78.5 kg of PBAT (weight average molecular weight 150,000) and 0.5 kg of allyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 0.1 kg of di-tert-butyl peroxide diisopropylbenzene, 0.5 kg of γ-methacryloyloxypropyltrimethoxysilane, 20 kg of montmorillonite, and 0.1 kg of tetraisopropyl di(dioctylphosphite)titanate. Mix them using a high-speed mixer at 800 rpm, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the extruder. Weigh 0.3 kg of glyceryl distearate and feed it into the twin-screw extruder through the second side feed port of the eighth section of the extruder.
[0043] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 500 r / min.
[0044] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0045] Infrared spectroscopy was performed on virgin PBAT, hydrophobic additives, crosslinking agents, and modified PBAT after 30 days of soaking. In Example 1, the hydrophobic additives were clearly retained at 2849.21 cm⁻¹ after soaking. -1 Crosslinking agent 2955.87cm -1The characteristic peaks indicate that some of the hydrophobic additives and crosslinking agents have reacted onto PBAT, resulting in the corresponding structure.
[0046] Example 2
[0047] Weigh 87.2 kg of PBAT (weight average molecular weight 120,000) and 1 kg of allyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 1 kg of γ-methacryloyloxypropyltrimethoxysilane, 0.1 kg of di-tert-butyl peroxide diisopropylbenzene, 10 kg of montmorillonite, and 0.1 kg of tetraisopropyl di(dioctylphosphite)titanate. Mix them using a high-speed mixer at 800 rpm, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the extruder. Weigh 0.6 kg of glyceryl distearate and feed it into the twin-screw extruder through the second side feed port of the eighth section of the extruder.
[0048] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 300 r / min.
[0049] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0050] Example 3
[0051] Weigh 82.6 kg of PBAT (weight average molecular weight 180,000) and 0.7 kg of allyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 0.7 kg of γ-methacryloyloxypropyltrimethoxysilane, 0.2 kg of di-tert-butylperoxide diisopropylbenzene, 15 kg of montmorillonite, and 0.3 kg of tetraisopropyl di(dioctylphosphite)titanate. Mix them using a high-speed mixer at 800 rpm, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the extruder. Weigh 0.5 kg of pentaerythritol distearate, and feed it into the twin-screw extruder through the second side feed port of the eighth section of the extruder.
[0052] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 600 r / min.
[0053] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0054] Example 4
[0055] Weigh 82.3 kg of PBAT (weight average molecular weight 150,000) and 0.7 kg of vinylbenzyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 0.7 kg of vinyltrimethoxysilane, 0.2 kg of dicumyl peroxide, 15 kg of montmorillonite, and 0.3 kg of tetraisopropyl di(dioctylphosphite)titanate. Mix them using a high-speed mixer at 800 rpm, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the extruder. Weigh 0.5 kg of glyceryl disorbate and feed it into the twin-screw extruder through the second side feed port of the eighth section of the extruder.
[0056] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 600 r / min.
[0057] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0058] Comparative Example 1
[0059] Compared with Example 1, the difference is that the hydrophobic additive and crosslinking agent were removed to verify their effect on barrier properties.
[0060] Weigh 79.1 kg of PBAT (weight average molecular weight 150,000) and 0.7 kg of allyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 0.1 kg of di-tert-butyl peroxide diisopropylbenzene, 20 kg of montmorillonite, and 0.1 kg of tetraisopropyl di(dioctylphosphite) titanate. Mix them using a high-speed mixer at 800 rpm, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the casing.
[0061] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 500 r / min.
[0062] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0063] Comparative Example 2
[0064] Compared with Example 2, the difference is that the crosslinking agent and co-crosslinking agent were removed to verify their impact on long-term barrier properties.
[0065] Weigh 89.2 kg of PBAT with a weight-average molecular weight of 150,000 and feed it into the main feed port of the twin-screw extruder. Weigh 0.1 kg of di-tert-butyl peroxide diisopropylbenzene, 10 kg of montmorillonite, and 0.1 kg of tetraisopropyl di(dioctylphosphite)titanate. Mix them using a high-speed mixer at a stirring speed of 800 r / min, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the casing. Weigh 0.6 kg of glyceryl distearate and feed it into the twin-screw extruder through the second side feed port of the eighth section of the casing.
[0066] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 300 r / min.
[0067] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0068] Comparative Example 3
[0069] Compared with Example 3, the difference is that the content of hydrophobic additives was reduced and the coating agent was removed. It was verified that when the amount of hydrophobic additives was insufficient, it could not spread to form a water-blocking layer and the film had no barrier effect.
[0070] Weigh 78.5 kg of PBAT (weight average molecular weight 150,000) and 0.6 kg of allyl glycidyl ether, mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 0.6 kg of γ-methacryloyloxypropyltrimethoxysilane, 0.1 kg of di-tert-butylperoxide diisopropylbenzene, and 20 kg of montmorillonite, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the casing. Weigh 0.2 kg of glycerol disorbate, and feed it into the twin-screw extruder through the second side feed port of the eighth section of the casing.
[0071] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 600 r / min.
[0072] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0073] Comparative Example 4
[0074] Compared with Example 1, the difference lies in the use of a mainstream water vapor barrier solution on the market.
[0075] Weigh 78.5 kg of PBAT (weight average molecular weight 150,000), 5 kg of PLA, and 0.3 kg of ADR4468 chain extender. Mix them for 5 minutes using a low-speed mixer at 20 rpm, and then feed them into the main feed port of the twin-screw extruder. Weigh 8 kg of montmorillonite, 2 kg of talc, and 2 kg of calcium carbonate, and feed them into the twin-screw extruder through the first side feed port of the fourth section of the machine barrel.
[0076] The twin-screw extruder is divided into 14 sections. Sections 1 to 5 are set to a temperature of 140℃ to melt the material. Sections 6 to 8 are the plasticizing and mixing section, with temperatures set at 150℃-160℃-160℃. Sections 9 to 14 are the metering section, with temperatures set at 160℃-160℃-160℃-180℃-210℃. The screw speed is set to 600 r / min.
[0077] The film is extruded using a blown film extrusion machine. The die diameter is 120mm, the screw length-to-diameter ratio is 32, the single screw has 5 zones, and the temperature settings are 140℃, 150℃, 160℃, 160℃, and 150℃ respectively. The blow-up ratio is set to 3, and the production capacity is set to 40kg / h. The film thickness is set to 0.003um.
[0078] Table 1 lists the test results of the mechanical and water-blocking properties of the materials obtained in the examples and comparative examples.
[0079] Table 1. Mechanical property results of materials in each embodiment and comparative example.
[0080]
[0081] The water vapor transmission coefficient of pure PBAT is approximately 3.6–4.0. Table 1 shows that the water vapor transmission coefficient of the sample examples is generally lower than 90% of that of pure PBAT film, approaching the water-blocking coefficient of PE film, thus meeting the requirements for water-blocking applications. Example 1, compared to Comparative Example 1, verifies that hydrophobic additives and crosslinking agents play a crucial role in water vapor barrier. The water-blocking efficiency of small molecule precipitation-forming films is significantly higher than that of mineral powder. In Example 2, compared to Comparative Example 2, the addition of crosslinking agents and co-crosslinking agents is key to long-lasting water-blocking performance. These agents greatly slow down the rate at which small molecule additives detach from the film surface, resulting in a high water-blocking retention rate even after long-term water exposure and drying. In Comparative Example 3, compared to Example 3, the removal of the coating agent significantly reduces the dispersion performance of the mineral powder, leading to a decrease in the mechanical properties of the film. Furthermore, it verifies that when the content of hydrophobic additives is low, they cannot spread and form a water-blocking film on the film surface, resulting in a significant decrease in water-blocking effect. This indirectly verifies that additives need to spread and form a film on the film surface to achieve water-blocking properties. Comparative Example 4 is a commonly used water vapor barrier solution for mulch films on the market. It uses sheet mineral powder to achieve water vapor barrier. Compared with Comparative Example 2, the water vapor permeability is higher and cannot meet the requirements for high water vapor barrier.
Claims
1. A long-lasting, highly water-resistant biodegradable film, characterized in that, The biodegradable film comprises the following components: 78.2-89.2 parts by weight of polybutylene adipate terephthalate (PBAT), 0.3-0.6 parts by weight of hydrophobic additive, 0.5-1 parts by weight of crosslinking agent, 0.5-1 parts by weight of co-crosslinking agent, 10-20 parts by weight of mineral powder, 0.1-0.3 parts by weight of initiator, and 0.1-0.3 parts by weight of coating agent; The crosslinking agent is a trimethoxysilane containing a double bond group; The crosslinking agent is an olefin glycidyl ether; The hydrophobic additive is a hydroxyl-functionalized alkyl ester; The coating agent is a coordination titanate.
2. The biodegradable film according to claim 1, characterized in that, The thin film comprises the following structure: Where m is an integer from 1 to 10, n is an integer from 1 to 10, and x is an integer from 10 to 30.
3. The biodegradable film according to claim 2, characterized in that, In the thin film structure, m is an integer from 2 to 8, n is an integer from 2 to 6, and x is an integer from 18 to 22.
4. The biodegradable film according to claim 1, characterized in that, The weight-average molecular weight of the PBAT is 80,000 to 230,000.
5. The biodegradable film according to claim 4, characterized in that, The weight-average molecular weight of the PBAT is 120,000 to 180,000.
6. The biodegradable film according to claim 1, characterized in that, The hydrophobic additive is one or more of glyceryl distearate, glyceryl monostearate, and glyceryl disorbate.
7. The biodegradable film according to claim 1, characterized in that, The crosslinking agent is γ-methacryloxypropyltrimethoxysilane and / or vinyltrimethoxysilane.
8. The biodegradable film according to claim 1, characterized in that, The co-crosslinking agent is vinyl benzyl glycidyl ether and / or allyl glycidyl ether.
9. The biodegradable film according to claim 8, characterized in that, The crosslinking agent is allyl glycidyl ether.
10. The biodegradable film according to claim 1, characterized in that, The mineral powder is montmorillonite with a layered structure.
11. The biodegradable film according to claim 10, characterized in that, The mineral powder is octadecyl quaternary ammonium salt modified montmorillonite.
12. The biodegradable film according to claim 1, characterized in that, The coating agent is tetraisopropyl di(dioctylphosphite)titanate.
13. The biodegradable film according to claim 1, characterized in that, The initiator is a peroxide initiator.
14. The biodegradable film according to claim 13, characterized in that, The initiator is bis(tert-butylperoxide)diisopropylbenzene.
15. A method for preparing a long-lasting, highly water-resistant biodegradable film, wherein the biodegradable film is the biodegradable film according to any one of claims 1-14, characterized in that, The method is as follows: S1: The crosslinking agent, initiator, mineral powder and coating aid are mixed evenly using a high-speed mixer, and then fed into the twin screw from the side feed port. S2: The hydrophobic additive is fed into the twin screw from the side feed port; S3: Mix PBAT and crosslinking agent using a low-speed mixer, and then feed the mixture into the main feed port of the twin-screw extruder; S4: Extruded by a twin-screw extruder, water-cooled, and granulated to obtain biodegradable long-lasting water-blocking composite material particles.
Citation Information
Patent Citations
High-barrier-property full-biodegradable mulching film and preparation method thereof
CN113754995A
Degradable barrier material and application thereof
CN114108383A
Preparation method of high-strength high-barrier biodegradable film
CN114163788A
Anti-ultraviolet and high-water-resistance PBAT (Polybutylene Adipate / Terephthalate) film and preparation method thereof
CN107936495A
Polyester compounds having enhanced hydrophobic surface properties
US20160130411A1